Role-Playing Game (RPG) and Environmental Education: Pathways toward sustainability paradigms - a theoretical essay - Almeida, Jhottan Emanuel Gregorio; Cardozo, Maria Eduarda; Pereira, Máriam Trierveiler (Latin American Journal of the Built Environment & Sustainability, 2026)
Objective – This article aims to reflect on the Role-Playing Game (RPG) as a pedagogical resource in Environmental Education, analyzing its formative potential for sustainability in the face of contemporary socio-environmental dilemmas. Methodology – To this end, a theoretical essay was conducted, grounded in critical reflection and in the conceptual articulation between sustainability as a paradigm, Critical Environmental Education, and studies on play and RPG as a cultural phenomenon and structured social system. Originality/Relevance – This study addresses a theoretical gap in which RPG is still predominantly approached from an instrumental or motivational perspective, proposing its problematization as a formative device capable of making explicit conflicts, competing interests, and societal projects implicated in the socio-environmental crisis. Its academic relevance lies in articulating playfulness, complexity, and critical formation for sustainability. Results – It is argued that RPG, by establishing a symbolic space regulated by rules and open to the negotiation of meanings, enables the experience of complex situations, the experimentation of social roles, and the problematization of power relations that permeate the society-nature relationship. Theoretical/Methodological Contributions – The study expands the understanding of RPG as a cultural and formative instance, articulating it with the assumptions of Critical Environmental Education and highlighting its potential as a participatory and transdisciplinary strategy. Social and Environmental Contributions – By reinforcing educational practices that promote critical reflection and active participation, the study contributes to the formation of subjects capable of understanding and intervening in the disputes that shape sustainability, strengthening educational processes committed to socio-environmental transformation.